(untitled) (Jurnal De Jure Muhammadiyah Cirebon, 2022)
Murder is a heinous act, even if committed by a minor it is a sad tragedy in a civilization.This makes children as the next generation of the nation, can feel the coldness of detention cells.This journal aims to review in terms of law, which then makes the fruit of thought where effective ways to provide learning for children who commit murder.Besides that, it also not only provides a legal action, but side by side with the fulfillment of rights that must be obtained by children in the judicial process.This research prioritizes data collection from the results of the analysis, where this type of research is called the normative method. The results of the juridical analysis of minors who commit the crime of murder, in the judicial process are still carried out in accordance with Indonesian state law which is regulated in Article 338 of the Criminal Code, Law on the Juvenile Criminal Justice System Number 11 of 2012.In addition, do not forget about the protection of rights that must be obtained by children even though they are suspects and this is stated in the Law on Child Protection Number 23 of 2002. Keyword : Child, Murder, Rights Protection.